Drug-induced lupus - Kavadichanda Chengappa G (Indian Journal of Rheumatology)
Drug-induced lupus erythematosus (DILE) is an important differential to consider in a clinical setting of mild lupus. Numerous drugs ranging from the classically described procainamide and hydralazine to novel biological agents such as anti-tumor necrosis factors and immune checkpoint inhibitors are implicated in causing DILE. Various pathophysiologic mechanisms such as decreased central tolerance, molecular cross-reactivity, and epigenetic modifications of immune cells are known to play a role in the precipitation of drug-induced autoimmunity. Early recognition and prompt withdrawal of the offending agent is often sufficient to treat these autoimmune manifestations. A thorough knowledge of DILE is essential to ensure better patient care and better understand the role of xenobiotics in precipitating autoimmunity.